Legal Analysis of Consumer Protection in E-commerce Transactions - Romdoni, Indi Auliya (Program Studi Doktor Ilmu Hukum Fakultas Hukum, 2024)
The development of information and communication technology has driven the growth of e-commerce significantly in Indonesia. However, this growth also brings new challenges regarding consumer protection. This article analyzes the legal aspects of consumer protection in e-commerce transactions in Indonesia, with a focus on the existing legal framework, challenges faced, and solutions that can be implemented to improve consumer protection. Law no. 8 of 1999 concerning Consumer Protection and Government Regulation no. 80 of 2019 concerning Trading Through Electronic Systems (PPMSE) is the main basis for this analysis. Some of the main challenges discussed include asymmetric information between business actors and consumers, weak supervision and law enforcement, and protection of consumers' personal data. To address these challenges, this article recommends increased regulation and oversight, consumer education, and the use of technology for consumer protection. Case studies of online fraud and personal data leaks are also presented to provide a concrete picture of the problems faced and the steps that can be taken to resolve them. The conclusion of this analysis emphasizes the importance of synergy between strong regulations, consumer education, and technological innovation to create a safe and protected e-commerce environment for consumers in Indonesia. Thus, implementing these strategies is expected to increase consumer confidence in e-commerce transactions and encourage sustainable growth.